Evolution of mitochondrial protein biogenesis - Kutik, Stephan; Stroud, David A.; Wiedemann, Nils; Pfanner, Nikolaus (Biochimica et biophysica acta, 2009)
Mitochondria and the nucleus are key features that distinguish eukaryotic cells from prokaryotic cells. Mitochondria originated from a bacterium that was endosymbiotically taken up by another cell more than a billion years ago. Subsequently, most mitochondrial genes were transferred and integrated into the host cell's genome, making the evolution of pathways for specific import of mitochondrial proteins necessary. The mitochondrial protein translocation machineries are composed of numerous subunits. Interestingly, many of these subunits are at least in part derived from bacterial proteins, although only few of them functioned in bacterial protein translocation. We propose that the primitive α-proteobacterium, which was once taken up by the eukaryote ancestor cell, contained a number of components that were utilized for the generation of mitochondrial import machineries. Many bacterial components of seemingly unrelated pathways were integrated to form the modern cooperative mitochondria-specific protein translocation system.